Joan Mitchell paintings 1979-1985 - Mitchell, Joan 1925-1992 (David Zwirner Books, 2024)
"Discover Joan Mitchell's powerful and dynamic work-spotlighted in this book as never before "An entry for one of the best shows of 2022. . . . Mitchell, then in her 50s, reaches peak form in gathering brushstrokes that flicker and burn like auras on fire." -Jerry Saltz, New York magazine This highly anticipated publication focuses on the years 1979 to 1985-a significant and deeply generative period within Joan Mitchell's decades-long career. As Mitchell became even more fully immersed in daily life at her property in Vétheuil, France-surrounded by lush gardens, and challenged and inspired by new creative relationships-her studio practice flourished and her work became even more ambitious and expansive. Executed in an increasingly bold palette, the works from this period exemplify Mitchell's nuanced mastery of composition, scale, and color. In addition to her large-scale abstract works, this publication features numerous smaller paintings and a selection of archival materials. Included in the book are several texts that complement the illustrated works. A new essay by the bestselling author Julie Otsuka recollects her encounters with Mitchell's paintings over the years. A fascinating conversation between Mitchell and the French philosopher Yves Michaud from 1986 is featured. Reflections by the artists Shinique Smith and Lily Stockman each explore a unique component of Mitchell's oeuvre or practice, underscoring Mitchell's continued influence on artists today."
"Published on the occasion of Joan Mitchell: Paintings, 1979-1985, David Zwirner, 537 West 20th Street, New York, November 3-December 17, 2022" -- Colophon
Keywords: Mitchell, Joan / 1925-1992 / Exhibitions; Painting, Abstract / United States / 20th century / Exhibitions; Abstract expressionism / United States / Exhibitions; Painting, American / 20th century / Exhibitions; Peinture abstraite / États-Unis / 20e siècle / Expositions; Expressionnisme abstrait / États-Unis / Expositions; Peinture américaine / 20e siècle / Expositions; exhibition catalogs; Exhibition catalogs; Catalogues d'exposition; Ausstellungskatalog -- David Zwirner -- 03.11.2022-17.12.2022 -- New York